BIOCHEMICAL CHANGES OF ELECTROLYTES AND TRACE ELEMENTS AMONG PATIENT WITH CORONAVIRUS DISEASE -19 (COVID -19) IN KHARTOUM STATE - Ali, Abdallah E; Sabil, Ahmed Jbril Aldooma; Ali, Mohammed Abd Elfatah Elamin; Mohammed, Ahmed Ibn Edriss; Elmahdi, Salih A (Global Journal of Medical and Health Science, 2023)
Background: coronavirus disease 2019 COVID-19 is a pandemic caused by severe acute syndrome coronavirus 2 (SARS-CoV-2) is respiratory and can be involved in multiorgan failure causes many biochemical changes in the human body, our study was designed to examine the serum level electrolytes and trace elements in COVID-19 patients and associated with severity of the disease. Materials and methods: Cross-sectional study includes 50 COVID-19 patients conducted during the period from December 2020 to April 2021 and 50 healthy as control group. Blood samples were collected from the study group and measured electrolytes sodium and potassium by easy lite, calcium, phosphate, zinc, and copper by using calorimeter methods, statistical analysis was conducted using the SPSS version. Results: The study showed that in COVID-19 patients there was a significantly low level of sodium (132 ± 4.3), potassium (3.2 ± 0.4), and calcium (7.8 ± .98) in comparison to control, insignificant in level of phosphorus and magnesium when compared with control group respectively ( P.value = 0.15 , 0.8 .) . There is significant decrease in the mean level of zinc and increase in the mean level of copper in COVID-19 patients when were compared to control group (p value = 0.000) ,. However there was strong correlation between sodium (r=-.753, p= .000) , potassium (r= -.736, p=.000) , Zinc (r= -.819, p= .000) and Copper (r= .700, p= .000) with severity of disease. Conclusions: COVID-19 infection cause hypernatremia, hypokalemia, and hypocalcaemia. Low zinc and high copper levels, the level of parameters is correlated with the severity of the disease.